Surgery Boot Camp - Nabil Issa; Jonathan Fryer; Mamta Swaroop; Daniel McCarthy; Jeffrey Wayne; Shari Meyerson; Debra DaRosa (Association of American Medical Colleges, 2014)
Abstract This resource is a 1-day course for incoming surgery residents to help decrease their anxiety and prepare them to their roles as surgical interns. The course is comprised of five distinct sessions with clear goals and objectives. Each session utilizes appropriate interactive techniques including direct questions, open discussions, roleplay, and simulation with structured debriefings to achieve its goals. The five sessions feature the SBAR (situation, background, assessment, recommendation) technique, answering pages, hand offs, advanced trauma life support, and a scavenger hunt. Residents described the course as important and enjoyable, and stated that it achieved its goals. The overall course rating was a 4.8 out of 5. Residents indicated that the course improved their self-confidence and understanding of their roles and duties. More residents passed the knowledge test after attending this boot camp (24% passed pretest versus 68% passed posttest).